Customary Leadership Amidst The Flow Of Modernity: The Voices Of Dayak Ma'anyan Youth In East Kutai - Prabowo, Heru; Ratulina, Triesna; Pongsibidang, Monica; Rukmana, Ovalia (Jurnal Indonesia Sosial Sains, 2025)
This research explores the dynamics of traditional leadership in the Ma'anyan Dayak community in East Kutai in the midst of modernity and digital transformation. Using a qualitative approach with interpretive phenomenological methods, this study delves into the subjective experience of an indigenous youth named TP in understanding, responding, and reflecting on changes to the values and structure of indigenous leadership in his community. The findings show that although the formal structure of indigenous leadership has experienced a decline in authority, basic values such as deliberation, mutual cooperation, respect for ancestors, and solidarity are still alive and maintained through cultural mechanisms. Youth play an important role in cultural revitalization, particularly through art studios, traditional craft training, and the use of social media as a space for documentation and informal education. Traditional leadership is no longer viewed only from the structural or hereditary side, but must have social credibility, personal charisma, and the ability to bridge local values with the demands of the times. Social media, for example, is an effective means of disseminating cultural values to the digital-native young generation. Theoretically, this research reinforces the concepts of symbolic leadership, charismatic authority, and mediatized traditions, which show that traditional leadership is not a static entity, but rather a dynamic and adaptive one. The main contribution of this study is to highlight the importance of local narratives as a form of resistance to cultural marginalization in national discourse as well as to open up space for community-based policies and interventions. With the active involvement of the younger generation and a participatory approach, indigenous leadership can remain relevant, live socially, and be part of the solution in building an empowered and dignified future of indigenous communities.